Fenologi Mangrove (Rhizophora apiculata, R. mucronata dan R.stylosa) di Pulau Unggas, Air Bangis Pasaman Barat, Sumatera Barat - Kamal, Eni (Jurnal Natur Indonesia, 2011)
Phenology of tropical forest plant is a population factor and does not include community factor, this is caused by a genetic determinationand also the influence of the environment. Phenology of plants in mangrove correlated with the time of flowering, fruiting, and productionof fruits or propagules. Phenology research in mangrove plants in the Unggas Island, West Pasaman, done with ‘tagging’ technique method.Signs made of plastic and are numbered. Data collection included from the formation of flower blooming, up to the formation of fruit orpropagules ripe. Phase of the development is categorized to two categories: (a) flower, and (b) fruit. The analysis method is the analysis ofvariance (ANOVA, p<0.01) and post-hoc test, Duncans Multiple Range Test (DMRT, p<0.01) to obtain comparison and differencesbetween the components of flower, flower fall, fruit, and fruit maturity.